Effects of Game and Poem-Enhanced Instructional Strategies on Pupils’ Learning Outcomes in Mathematics in Bayelsa State, Nigeria (2014)
Mathematics is a core and compulsory school subject from primary through the senior secondary school level. Reports from examination bodies have shown that the mean score of Bayelsa State pupils’ achievement in mathematics is below average. This has been attributed to the lecture instructional strategy being adopted by the teachers of the subject. Therefore, game- and poem-enhanced instructional strategies have been recommended to improve mathematics instruction at the primary school level but few studies have been carried out to determine the effectiveness of these strategies. Therefore, this study, determined the effects of game- and poem-enhanced instructional strategies on pupils’ achievement, knowledge of mathematics concepts and interest in mathematics. The moderating effects of verbal ability and gender were also determined. A pretest-posttest, control group, quasi-experimental design with 3x3x2 factorial matrix was adopted. Three hundred and forty-four primary six pupils from twelve purposively selected public schools in Yenagoa and Ogbia Local Government Areas of Bayelsa State were randomly assigned to two treatments and control groups. The study lasted for twelve weeks. The instruments used were two teachers’ assessment sheets, instructional guides on Poem-Enhanced Instructional Strategy (PEIS) and Game-Enhanced Instructional Strategy (GEIS) for the experimental groups and Modified Lecture Instructional Strategy (MLIS) for control groups, Pupils’ Mathematics Achievement Test (r=0.72), Pupils’ Mathematics Concepts Test (r=0.81), Pupils’ Interest in Mathematics Inventory (r=0.73) and Pupils’ Verbal Ability Test (r=0.85). Seven null hypotheses were tested at 0.05 level of significance. Data were analysed using Analysis of Covariance (ANCOVA) and Scheffe Post-hoc analysis. Treatment had significant main effect on pupils’ achievement in mathematics (F(2,325)=142.473; ɳ2=0.467), knowledge of mathematics concepts (F(2,325)=81.115;2=0.333) and interest in mathematics (F(2,325)=163.003; 2=0.501). GEIS group performed better on achievement in mathematics (=17.42) than PEIS group (=16.40) and MLIS groups (=12.91). The PEIS had higher posttest mean score on pupils’ knowledge of mathematics concepts (=14.43) than GEIS (= 13.44) and MLIS group (=10.57). Also, PEIS had higher posttest mean score on interest in mathematics (=15.36) than GEIS group (=14.41) and MLIS (=10.77) groups. Verbal ability had significant main effect on pupils’ achievement in mathematics (F(2,325)=35.939;2=0.181), knowledge of mathematics concepts F(2,325)=5.777;2=0.034) and interest in mathematics (F(2, 325)=19.320;2=0.106). The posttest mean scores on pupils’ achievement in mathematics by verbal ability were high (=16.80), medium (=15.99) and low (=13.95). Similarly, the posttest mean scores on pupils’ knowledge of mathematics concepts by verbal ability were high (=13.58), medium (=12.80) and low (=12.06). Also, the posttest mean scores on pupils’ interest in mathematics by verbal ability were high (=14.26), medium (=13.76) and low (=12.52). There was significant interaction effect of treatment and verbal ability on pupils’ knowledge of mathematics concepts (F(4,325)=2.731;2=0.033). Game-enhanced instructional strategy is most effective in improving pupils’ achievement in mathematics, while poem-enhanced instructional strategy is most effective in improving pupils’ knowledge of mathematics concepts and interest in mathematics. Primary school teachers and curriculum developers should adopt these strategies to improve pupils’ learning outcomes in mathematics.